Bede's temple: an image and its interpretation - O'Brien, C (2013)
This thesis studies, for the first time, Bede’s use of the image of the Jewish temple across all his writings. Not only analysing how Bede developed earlier Christian interpretations of the temple, it also uses the temple-image to shine light on under-explored aspects of his theological thought. Throughout, I argue that the communal understanding of the temple-image in Bede’s monastery helped shape his exegesis; we should think of Bede, not as an individual scholar, but as a monk engaged in an active discourse concerning the Bible. Chapter 1 introduces the thesis, providing the historiographical and historical context. Bede’s exegesis existed within a long tradition of Christian interpretation of the temple, as Chapter 2 shows; one image could be interpreted in diverse ways by Bede and therefore this thesis follows a thematic approach. Chapter 3 studies Bede’s engagement with the cosmic interpretation of the temple, in particular his use of the image to emphasise the Anglo-Saxons’ participation in the universal Church. Analysing Bede’s interpretation of the Jewish priesthood, Chapter 4 argues that he championed an élite of ordained clerics in the role of reforming the temple-Church. This Church clashed with the Body of Satan, symbolised by the Tower of Babel, concerning which the contemporary Northumbrian situation shaped Bede’s understanding. For Bede, the temple-image stressed Christ’s humanity and his sacrificial priesthood, as Chapter 5 shows. Bede urged the faithful to shape themselves as pure temples in imitation of Christ, directing them towards union with God. A diachronic overview of Bede’s writings on the temple in Chapter 6 highlights the importance of the years immediately prior to 716, the period in which the Codex Amiatinus was created at his monastery of Wearmouth-Jarrow, in the development of Bede’s interpretation of the temple. We should consider the possibility that Bede’s temple-commentaries drew upon interpretations formed in this communal, monastic, context.